IMPLEMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE TALKING STICK PADA MATA PELAJARAN PAI DALAM PENINGKATAN HASIL BELAJAR PAI SISWA DI SDN CILOLOHAN KOTA TASIKMALAYA - Via Riftiani; Permadi, Rudi (HASBUNA : Jurnal Pendidikan Islam, 2025)
This Study aims to determine how the implementation of the Talking Stick cooperative learning model in islamic Relagious Education (PAI) subject improves student learning outcomes at SDN Cilolohan, Tasikmalaya City. The method used is qualitative research with data collection techniques through observation, interviews, and documentation. The result of the study indicate the use of the Talking Stick model makes student more active, dare to ask and answer questions, and more focused on following the lesson. Increased student involvement has an impact on increasing the average value of learning outcomes, especially in understanding religious material. Supporting factors for the success og this model include teacher motivation, adequate learning facilities, and positive responses from student. The inhibiting factors are student nervousness, time contraints, and diffrences in ability levels between students. Thus,the Talking Stick model is effectively applied in PAI learning to improve students learning outcomes, as long as it implemented with the right strategy according to class conditions.